THE GROWTH AND SURVIVAL RATE OF TIGER SHRIMP (Penaeus monodon) WITH THE ADDITION OF CALCIUM CARBONATE (CaCO3) - Adhar '; Rusliadi '; Iskandar ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This study was conducted on April 12 until May 12, 2016 at the Brackish Water Aquaculture Development Centre Ujung Batee, Aceh Province. The aims of this study were to determine the growth and survival rate of tiger shrimp (Penaeus monodon) with the addition of calcium carbonate (CaCO3) and the amount of calcium carbonate (CaCO3) needed for the growth and survival rate of tiger shrimp (Penaeus monodon). This study was used an experimental completely randomized design method with 1 factor, 6 treatments and 3 replications. The treatment simbolized by P0 (without the addition of CaCO3), P1 (20 mg/L), P2 (35 mg/L), P3 (50 mg/L), P4 (65 mg/L) and P5 (80 mg/L). The results of this study showed that the best treatment contained in P4 (65 mg/L) with the absolute length of 2,78 cm, the absolute growth weight of 0.295 g, the survival rate (SR) were 85%, the daily growth rate (SGR) were 6,63% and as many as 58 individuals moulting intensity. Meanwhile, the water quality is still good for shrimp to grow.Keywords: Tiger shrimp (Penaeus monodon), Calcium Carbonate (CaCO3), moulting, survival rate